2017
DOI: 10.1371/journal.pone.0172357
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and genotyping of enteroviruses from CSF samples of patients with suspected sepsis-like illness and/or aseptic meningitis from 2012 to 2015 in West Bank, Palestine

Abstract: BackgroundHuman enteroviruses (HEVs) are the most frequently reported cause of aseptic meningitis with or without CSF pleocytosis in childhood. Rapid detection and genotype of HEVs is essential to determine the causative agent and variant causing sepsis-like illness and/or aseptic meningitis.AimTo investigate the molecular epidemiology of enteroviruses (EVs) among patients with sepsis-like illness and/or aseptic meningitis admitted to three major hospitals in West Bank, Palestine from 2012 to 2015.MethodsDurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
28
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 31 publications
10
28
4
Order By: Relevance
“…So far, only one report in Palestine confirmed the isolation of 7 different enteroviruses genotypes including echovirus 13, 14, 9, 30, 16, 6 and coxsackievirus B5 from sporadic cases of aseptic meningitis and/or sepsis like illness[10]. In the present study, all of the HEV positive cases occurred in children less than 7 years old and 50% of them < 1-year-old.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…So far, only one report in Palestine confirmed the isolation of 7 different enteroviruses genotypes including echovirus 13, 14, 9, 30, 16, 6 and coxsackievirus B5 from sporadic cases of aseptic meningitis and/or sepsis like illness[10]. In the present study, all of the HEV positive cases occurred in children less than 7 years old and 50% of them < 1-year-old.…”
Section: Discussionsupporting
confidence: 67%
“…In the present study, all of the HEV positive cases occurred in children less than 7 years old and 50% of them < 1-year-old. Highest rate of enterovirus-positive cases was reported previously in children less than 1 year of age in Palestine, United States, and Korea [10, 38]. On the contrary, other studies, reported that HEV aseptic meningitis occurs most frequently in patients with age range of 3–12 years’ old [13-15, 39].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations